Analysis of Irrigated Crops in Regions with Overexploited Water Sources: Case Aguascalientes, Ags, Mexico - Ledesma-Carrión, Dora Elena (Archives of Business Research, 2022)
There are few crop options for arid and semi-arid soils with annual rainfall of less than five hundred millimeters. Irrigated crops are supplied by rivers, dams, and aquifers. Due to climate change, rainfall has significantly changed its start of the season, frequency, and intensity. This causes problems in the recharge of aquifers and intensive extraction of water, putting the availability of the liquid in check to ensure the total development of the crop. What are the crops that should be replaced by more suitable ones? Which plants should no longer be cultivated? To answer these questions, optimization techniques and cross elasticities were applied, maximizing the value of production subject to the minimum water requirements that ensure the total development of the crop. Some perennial crops showed that they could be replaced, and other seasonal ones should not be cultivated in the coming years. The study was done at the regional level given the access to public and free information.